Literacy as an Effective Media for Distance Learning - Sinta Diana Martaulina; Selvie Sianipar; Riodinar Harianja (research, training and philanthropy institution Natural Aceh, 2021)
The emergence of the phenomenon of distance learning as online learning during the pandemic is concerned about the quality of achieving learning objectives. Finally, distance learning becomes an option so that the implementation of higher education can still be carried out like conventional learning. This restlessness opens opportunities for literacy methods as an effective medium in distance learning. The purpose of this research is to explain that literacy is not limited to reading and writing skills. Familiarize students with reading and accessing information before learning is a positive habit for organizing the brain and critical analysis skills. The research method used in research during this pandemic is a literature study